Optical manipulation of biological cell without measurement of cell velocity - Cheah, Chien Chern (2014)
Optical tweezer is a useful tool for non-contact micromanipulation tasks because it can manipulate biological cells precisely without causing damage to the cells. In many optical manipulation techniques, the measurement of the velocity of the cell is necessary. Since it is difficult to measure the velocity of the cell, the velocity information is usually obtained by differentiating the position of the cell in image space, which may result in degraded performance of the control system due to estimation error and the noises induced in differentiation. In this paper, an adaptive observer technique is proposed for optical manipulation of cell with a low Reynolds’ number, without measurement of the velocity of the cell. By using the proposed observer technique, a desired position input of the laser beam without measurement of the velocity of the cell is also developed. The stability of closed-loop system is analyzed by using Lyapunov-like method. Experimental results are presented to illustrate the performance of the proposed control method.